The dumb side to dumpsites - Abd Razak, Dzulkifli (2006)
Nowadays, mega projects are hardly in the news, except the one about a bridge that is not to be. Today’s headlines tend to be more on the megamess of sorts, viz environmental degradation, polluted air and rivers, smelly water and, more recently, poorly managed dumpsites. These give the impression that our development thus far has not been balanced and, less still, sustainable. Take the case of the Sungai Kembong open dumpsite near Semenyih, for example. This is a preIndependence dumpsite, over 50 years old, built at a time when there were no laws to govern its construction and maintenance.